Factors Affecting Employee Performance : A Case Study of PT. Bank Mandiri, Tbk In Baturaja Cluster, Oku District - Kartini, Putu; Oktarina, Yetty; Efrianti, Rini (BIMA Journal (Business, Management, & Accounting Journal), 2024)
Purpose: This study aims to analyze the factors affecting employee performance at Bank Mandiri, Tbk. Methodology: A quantitative descriptive method was employed, using a sample of 61 employees in the Baturaja cluster. Data were analyzed using multiple linear regression with SPSS 21. Results: The results reveal that work discipline, motivation, and facilities and infrastructure significantly influence employee performance. Conversely, the work environment does not significantly affect employee performance due to employees' high adaptability and ability to work effectively in diverse conditions. Findings: This study highlights that internal factors like discipline and motivation play a more critical role in enhancing employee performance than external factors like the work environment. Originality: This research provides insights specific to Bank Mandiri employees, offering practical implications for improving employee performance in banking. Novelty: The findings emphasize the reduced influence of external factors, such as the work environment, in highly adaptable teams. Conclusions: Work discipline, motivation, and infrastructure are key drivers of employee performance, while adaptability minimizes environmental influence. Type of Paper: Quantitative descriptive research paper.